Elucidating the multiscale mechanisms and therapeutic targets of caffeic acid in gastric cancer: a synergy of computational and experimental approaches - Zhang, Hongrong; Li, Yufan; Li, Ya (Frontiers in Molecular Biosciences, 2025)
IntroductionGastric cancer is a malignant tumor with high incidence and mortality rates worldwide, and effective therapeutic strategies targeting its complex pathological processes are limited. Caffeic acid is a phenolic compound derived from natural plants and has attracted attention for its potential anticancer properties; however, its mechanism of action in gastric cancer has not been fully elucidated.MethodsIn this study, a multimodal computational framework integrating multiomics, machine learning, and molecular dynamics simulations, combined with in vitro experiments, was used to systematically investigate the molecular mechanism of caffeic acid against gastric cancer.ResultsAmong the predicted targets, FZD2—a major receptor that mediates noncanonical WNT/Ca2+ signaling—was identified as a core regulatory hub associated with tumor progression and metastasis. Molecular dynamics simulations further revealed a stable binding interaction between caffeic acid and FZD2. An in vitro EMT model was established by treating human gastric cancer cells with TGF-β1. The results showed that caffeic acid intervention inhibited cell migration, invasion, and EMT progression while reducing FZD2 protein expression.DiscussionThis study confirmed that caffeic acid regulates FZD2 expression and inhibits the activation of the noncanonical Wnt5a/Ca2+/NFAT signaling pathway, thereby interfering with gastric cancer–related pathological processes. These findings reveal the molecular mechanism of caffeic acid in gastric cancer and reflect the value of natural products in cancer research.